Sarcopenic obesity, nutritional status and lipid profile of chronic renal patients undergoing hemodialysis (Research, Society and Development, 2022)
This study aimed to establish the frequency of Sarcopenic Obesity and to analyze the association with nutritional status, lipid profile, lifestyle and comorbidities in patients with chronic kidney disease undergoing hemodialysis. This is a cross-sectional study with 102 adult and elderly patients with chronic kidney disease undergoing hemodialysis, evaluated from January to October 2016, in the city of Recife-PE. The Sarcopenic Obesity was defined from the concomitant presence of sarcopenia and high percentage of body fat. Sociodemographic, anthropometric, body composition, clinical, biochemical and lifestyle variables were also evaluated. Differences between groups were assessed using Student's T and Mann Whitney U tests. To assess the association between the variables and Sarcopenic Obesity, the Chi-Square and Fisher's Exact tests were used. All analyzes were performed using a significance level of 5% and the statistical program used was R (version 4.0.1). The frequency of OS identified was 53.9%, which was associated with sex (p